The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.chemmater.2c03659
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Transformation Pathways in Semiconductor Clusters by Studying the Formation of Spectroscopically Pure (CdS)13 Magic-Size Clusters

Abstract: The transformation pathways in cluster regions have received only limited attention, and the fundamental issues involved require in-depth study. Here, we demonstrate the formation and transformation mechanisms in Cd-based MSCs by studying spectroscopically pure (CdS) 13 MSCs. We show that the molecular formula of the obtained CdS MSCs is [(CdS) 13 (RNH 2 ) 13 ] and that the experimental estimate of the diameter is approximately 0.75 nm. Further study reveals that, in addition to the amine-bilayer templated syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…On this basis, the as-obtained (CdS) 13 MSCs could act as a single precursor to form colloidal CdS nanoplatelets with a wurtzite structure. 49 In addition, Yu et al 50 demonstrated for the first time how colloidal semiconductor MSCs undergo isomerization at low temperatures under external chemical stimuli, namely, MSC-399 to MSC-422. Notably, ion exchange makes it possible for as-obtained MSCs to transform into their counterparts, indicating that new MSCs can be synthesized via a template-based approach (see Fig.…”
Section: Synthesis and Growth Mechanism Of Typical Ii–vi Mscsmentioning
confidence: 99%
“…On this basis, the as-obtained (CdS) 13 MSCs could act as a single precursor to form colloidal CdS nanoplatelets with a wurtzite structure. 49 In addition, Yu et al 50 demonstrated for the first time how colloidal semiconductor MSCs undergo isomerization at low temperatures under external chemical stimuli, namely, MSC-399 to MSC-422. Notably, ion exchange makes it possible for as-obtained MSCs to transform into their counterparts, indicating that new MSCs can be synthesized via a template-based approach (see Fig.…”
Section: Synthesis and Growth Mechanism Of Typical Ii–vi Mscsmentioning
confidence: 99%
“…Table S2 recapitulates the various Cd to S number ratios and core compositions reported for CdS MSC-322 and MSC-311; further effort will be required to fully characterize their compositions and structures. [11,16,[28][29][30][31][32] In Figure 3b, XRD patterns are shown for MSC-322 (trace 1), MSC-328 (trace 2), and MSC-373 (trace 3). The diffraction pattern of MSC-322 differs from those of MSC-328 and MSC-373, which are relatively similar.…”
Section: Characterization Including Maldi-tof Ms Xrd and Ftirmentioning
confidence: 99%
“…In this work, a complete anion exchange process in CdSe, CdS, and CdTe MSCs was achieved for the first time under mild conditions, and the intrinsic transformation mechanism was systematically investigated. We proposed that covalent inorganic complexes (CICs) played a critical role as intermediates in the intermolecular transition of template-free MSCs (nonstoichiometric composition), which was distinct from the intramolecular anion exchange process found in templated MSCs (stoichiometric composition). , An in situ absorption spectroscopy study showed that the conversion pathway from CdE 1 -MSCs to CdE 2 -MSCs (Scheme ) involved three key steps, namely the disassembly of CdE 1 -MSCs into CdE 1 -CICs (step 1, eq ), the anion exchange reaction that transformed CdE 1 -CICs into CdE 2 -CICs (step 2, eq ), and the assembly of CdE 2 -CICs into CdE 2 -MSCs (step 3, eq ). Steps 1 and 2 were relatively fast, and step 3 was a rate-determining step, following the behavior of first-order reaction kinetics with a rate constant ( k 1 ) of 0.01 min –1 ( t 1/2 of 69.3 min), which was five times faster than the rate constant of the anion exchange reaction in templated MSCs.…”
Section: Introductionmentioning
confidence: 99%